The Shelf life Prediction of Sorghum Modified Flour Crackers Using Critical Moisture Approach - Ulya Sarofa; Riski Ayu Anggreini (International Journal of Advance Tropical Food, 2019)
The objectives of this research were to produce crackers based on sorghum modified flour and to predict its shelf life using a critical moisture approach. The research was conducted in two stages. The first stage was to determine the best crackers of nine formulations. The second stage was to predict the shelf life of the best crackers formulation by using a critical moisture content approach. The best crackers were produced from a mixture of 50% sorghum modified flour, 50% wheat flour and 25% margarine. The products had a puffing ratio of 38,04 %, and hardness of 28.86 N. The moisture sorption isotherm curve of sorghum modified flour crackers could be described using a Hasley model. Using the critical moisture approach, sorghum modified flour crackers packaged in a metalized plastic and stored at 30°C and stored at 84% relative humidity, the product shelf life would be 207 days.